A DIALOGICIDADE INTERCULTURAL DAS MÚLTIPLAS FORMAÇÕES DOCENTES PARA O TRABALHO DE ENSINO DECOLONIZADO - Fernnades de Oliveira, Marcia Maria; Lopes de Freitas, Maria Fernanda (Revista Eletrônica Científica Ensino Interdisciplinar, 2022)
This essay brings theoretical reflections on the intercultural dialogicity of multiple teacher training for decolonized teaching work, focusing on the formative tripod of formal, non-formal and informal education as a basis for initial teaching and as a possibility for decolonized teaching work. The beginning of teaching practice stands out, when we teach through the knowledge of the experiences and readings of the world. This knowledge is recognized in national policies for teacher training and is built by informal and non-formal education, being also fundamental for the work of decolonized teaching. With this study, we hope to gather elements for discussions about possibilities of creating environments to value the knowledge lived, thinking about the construction of curricula that dialogue with territories that need to be occupied, aiming at cultural diversity permeated with elements of the real, local and experiences.